Insufficient reply by Hermida et al. to the critical comments to the MAPEC and HYGIA studies - Lemmer, Björn; Middeke, Martin (Chronobiology international, 2020)
The reply of Hermida et al. (2020) to our critical comments on the MAPEC and HYGIA Lemmer and Middeke (2020) studies in this Journal is insufficient and incomplete. Hermida does not address our first and main point on the baseline blood pressure values of 131/77 mmHg over 48 hours comprising 57.4% of the treated hypertensives (according to Table 1 in HYGIA) and consequently 42.6% of the untretated hypertensives! We criticized that in the HYGIA study; both normal and treated patients were included in one group not separated by statistics and without information on the baseline blood pressure values in each subgroup. This basic failure is our key issue of criticism and the basis of unreliability concerning the whole publication. This issue was not picked up in the recent comment of Hermida et al. (2020). They just concentrated on minor points in order to reject our severe criticism.
Gesehen am 11.11.2025